Eusebius and the Jewish Authors: His Citation Technique in an Apologetic Context. By Sabrina Inowlocki - Whealey, Alice (The journal of theological studies, 2008)
This is a welcome in-depth treatment of Eusebius of Caesarea's citation and use of non-biblical Greek-language Jewish prose writers in his apologetic magnum opus, the Apodeixis, more commonly known by the titles of its two component parts, Praeparatio Evangelica and Demonstratio Evangelica. The Jewish writers are Aristobulus, Philo of Alexandria, Josephus, and the so-called ‘minor’ Jewish authors, who, according to Inowlocki, were known to Eusebius only through the compilation of Alexander Polyhistor. Inowlocki also examines Eusebius’ use of Pseudo-Aristeas, although she notes that Eusebius erroneously believed him to be a pagan.